The Diaspora Descendants of Sayid Alwi Danuningrat Basyaiban Magelang - Rosyid Abdul Majid; Apipuddin Apipuddin (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This study aims to reveal the diaspora of sayid alwi Basyaiban's descendants who have a long history, unique process, and strong influence in the Javanese aristocratic system, especially in the Ngayogyakarta palace and the process of establishing Magelang as an administrative city. This article attempts to explain the diaspora process of the Basyaiban family in Magelang from Hadramaut to Magelang. The researcher uses the historical method. The approach used in this study is the genealogical approach and theory from Hall, namely: Representation and Cultural Identity in compiling this paper. The findings from this study indicate that, first: the Basyaiban family belongs to the Alawiyyin Hadramaut group from Sayid Abubakar ibn Muhammad Basyaiban's genealogy. Second: Sayid Abdurrahman ibn Umar Basyaiban was the person who first came to Indonesia on the recommendation of Sunan Gunung Jati to take care of the mosque in Cirebon. Third: Sayid Ahmad ibn Muhammad Basyaiban has carried out the unification of the Basyaiban family with the Ngayogyakarta palace. His son, Sayid Alwi Basyaiban, was appointed as the first regent of Magelang with the title Danuningrat I. Then this position was continued by his descendants up to the 5th regent. Fourth: the Basyaiban family between the time of Sunan Gunung Jati, namely Sayid Sulaiman Basyaiban (Prince Kanigoro) 1053 H and the time of Sayid Alwi ibn Ahmad Basyaiban (Danuningrat I) 1241 H in the Ngyogyakarta region had a point in common with the awarding of Javanese titles and names from natives. Sayid Ahmad ibn Muhammad Basyaiban had unified the Basyaiban family with the Ngayogyakarta palace. The result of the adaptation of the Basyaiban family was the appointment of Sayid Alwi Ibn Ahmad Ibn Muhammad Basyaiban as the first regent of Magelang with the title Danuningrat I. Then this position was continued by his descendants up to the 5th regent.